The influence of ice crystals on the evolution of run-back ice in mixed icing conditions. (June 2020) - Kashevarov, A V; Miller, A B; Potapov, Yu F; Stasenko, A L; Tokarev, O D; Zhbanov, V A
Abstract: In the framework of the development of physical and mathematical models of icing in crystalline and mixed conditions and their verification, the effect of ice crystals in the airflow on the evolution of run-back ice on the surface of a wing model for tests in icing facility is numerically studied. The results confirm that the experimentally observed change in the mass of ice deposits with the introduction of crystals into the flow is associated with the absorption of a part of the mass of crystals by the film at low flow rates and with the film splashing at higher speeds.